Monitoring Of Natural Heat Occurrence At The Bear Canyon Coal Mine - Jacob O. Kingston; Miles T. Stephens; Felipe Calizaya (Society for Mining, Metallurgy & Exploration, 2005)
Currently, the Bear Canyon Mine is facing the challenge of excessively high coal and rock temperatures in one of its headings. In Mine No.3, the air temperature at the 6th Right panel reached 36.4ºC and the coal 83.9 ºC. Due to these severe work conditions, the mining plan has been altered by changing the mine direction to avoid the high temperatures. To investigate the problem, drill holes were developed from the entries and the rock temperatures monitored using K-type thermocouples. The measurements confirmed the existence of localized “hot spots” in the mine. This paper presents a summary of ventilation surveys that were conducted in this mine. It includes the results of coal and rock temperature measurements from drill holes, interpretation of results using a heat flow simulator and the identification of hot spot areas. It also includes a summary of methods that were developed to reduce the hazard and control the problem.